BIOCONTROL EFFICACY OF OPERCULINA TURPETHUM (L.) (CONVOLVULACEAE) LEAF EXTRACTIVES AGAINST LARVAL FORM OF MALARIAL MOSQUITO ANOPHELES STEPHENSI (LISTON 1901) - KUNTAL BHATTACHARYA; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Vector control is the foremost step to diminish the mosquito borne diseases as the proper vaccinations are yet to develop against those obnoxious diseases. After many resistant cases, it is important to develop other sources of eco-friendly insecticides. The present piece of study was designed to evaluate the mosquito larvicidal efficacy of Operculina turpethum against malarial vector Anopheles stephensi. Hot and cold aqueous leaf extracts, and two different solvent extracts were treated against all the larval instars. LC50 and LC90 values were determined. Statistical justifications were made by log-probit, regression and ANOVA analyses. Cent percent mortality was found against 1st instar larvae at a concentration of 0.5% hot aqueous and 160 ppm solvent extracts after 72 h of exposure. Non-target organisms were nonresponsive after treatment with the same. From the present study it can be concluded that the bioactive fractions from O. turpethum leave extracts have remarkable mosquito larvicidal potentiality.